Small subcortical ischemic infarction and other DWI lesions establish predictive model for MES - Zhao, Liming; Xu, Yicheng; Zhao, Hongqin; Wang, Senlin; Zhang, Jiatang; Tian, Chenglin; Zhang, Aijuan; Zhang, Zengchao; Ji, Tailing; Wang, Zhengang (Frontiers in Neurology, 2025)
ObjectiveThe relationship between small subcortical ischemic infarction remains poorly characterized. Therefore, the present study aimed to investigate the association between artery-to-artery embolization and small subcortical infarctions.MethodsThis retrospective observational cross-sectional study enrolling 230 patients with acute middle cerebral artery (MCA) stroke classified into the microembolic signals-positive (MES+) and MES-negative (MES−) groups. The diffusion weighted imaging (DWI) infarction patterns in the MCA were divided into the territorial, border zone (BZ), cortical, and subcortical infarcts. We set the standard of small subcortical infarction (SCI) into two levels: < 10 mm diameter and <5 mm diameter. Relevant DWI parameters were used to build a nomogram for MES+, using free statistics.ResultsMES occurred in 38 of the 230 cases, yielding a positivity rate of 16.5%. BZ, SCI <10 mm, cortical ischemia (CI), stenosis, white blood cell count, and gender were compared between the MES+ and MES− groups. Multivariate analysis revealed that BZ, SCI < 10 mm, and CI were independently associated with MES. Based on DWI parameters, a nomogram model was built for MES+. The area under the curve of the model was 0.826 (95%CI 0.764 to 0.889). In internal cross-validation, the slope of the calibration curve was 1.000, indicating that the model accurately predicted unsuccessful treatment outcomes.ConclusionSmall subcortical infarctions are associated with MES. In the present study, we built a predictive nomogram model for MES+ based on small subcortical infarctions and other DWI parameters. This model demonstrated good performance in clinical practice.